2023
DOI: 10.3389/fpubh.2023.1131753
|View full text |Cite
|
Sign up to set email alerts
|

Surface ozone pollution in China: Trends, exposure risks, and drivers

Abstract: IntroductionWithin the context of the yearly improvement of particulate matter (PM) pollution in Chinese cities, Surface ozone (O3) concentrations are increasing instead of decreasing and are becoming the second most important air pollutant after PM. Long-term exposure to high concentrations of O3 can have adverse effects on human health. In-depth investigation of the spatiotemporal patterns, exposure risks, and drivers of O3 is relevant for assessing the future health burden of O3 pollution and implementing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…A study in nine cities worldwide 43 indicated that low wind speeds, increase in maximum temperatures, and decrease in relative humidity would also lead to the increase in O 3 during COVID-19. Regarding long-term trends, the annual average concentration of O 3 in China significantly increased at a rate of 1.84 µg/m 3 from 2013 to 2018 and peaked in 2018; O 3 has become the second most abundant air pollutant after PM 44 . In Gansu Province, the number of summer days with O 3 as the dominant pollutant increased from 77.8% in P-I to 89.2% in P-II.…”
Section: Discussionmentioning
confidence: 99%
“…A study in nine cities worldwide 43 indicated that low wind speeds, increase in maximum temperatures, and decrease in relative humidity would also lead to the increase in O 3 during COVID-19. Regarding long-term trends, the annual average concentration of O 3 in China significantly increased at a rate of 1.84 µg/m 3 from 2013 to 2018 and peaked in 2018; O 3 has become the second most abundant air pollutant after PM 44 . In Gansu Province, the number of summer days with O 3 as the dominant pollutant increased from 77.8% in P-I to 89.2% in P-II.…”
Section: Discussionmentioning
confidence: 99%